-5x-2(4-2x)=2+7

Simple and best practice solution for -5x-2(4-2x)=2+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x-2(4-2x)=2+7 equation:


Simplifying
-5x + -2(4 + -2x) = 2 + 7
-5x + (4 * -2 + -2x * -2) = 2 + 7
-5x + (-8 + 4x) = 2 + 7

Reorder the terms:
-8 + -5x + 4x = 2 + 7

Combine like terms: -5x + 4x = -1x
-8 + -1x = 2 + 7

Combine like terms: 2 + 7 = 9
-8 + -1x = 9

Solving
-8 + -1x = 9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + -1x = 9 + 8

Combine like terms: -8 + 8 = 0
0 + -1x = 9 + 8
-1x = 9 + 8

Combine like terms: 9 + 8 = 17
-1x = 17

Divide each side by '-1'.
x = -17

Simplifying
x = -17

See similar equations:

| 15+.20m=25.00+.10m | | x+8+16=0 | | (q-5)*2= | | -5-2(4-2x)=2+7 | | 2x+44=x-12 | | 2(w-6)+2(w)=3(w+8) | | (e+5)*4= | | 0.5(2n+6)=0.2(8n-10) | | Y+-12=11 | | 5.95+0.06m=30 | | 4+11y-1=9y+21-7y | | 8(X-4)=350 | | 42-4X=200 | | 1-x=.4 | | 1.5(x+8)=5.7+0.6x | | 5x+113=11x-7 | | 2x-(5x+2)=9x-26 | | 3y-5=-8(6+5t) | | 11(t-3)+3t=7(2t+4)-10 | | 4x-7=-2x-19 | | 8.99(85)=650+x | | 6+25x=20x+8 | | 8(x-5)-6x=-26 | | 0.5x(y-z)= | | 5.45=14.8-2.2t | | -22=4w+2(w+4) | | y+24=11 | | 7(3x+6)=21x-10 | | (p+7)(-2)= | | -33=5(v-3)-2v | | x=-1/2*4 | | 8.99(x)=1050+335 |

Equations solver categories